The NADase CD38 is a central regulator in gouty inflammation and a novel druggable therapeutic target - Paulo Gil Alabarse; Patricia Oliveira; Huaping Qin; Tiffany Yan; Marie Migaud; Robert Terkeltaub; Ru Liu-Bryan (Inflammation Research, 2024)
Objectives Cellular NAD + declines in inflammatory states associated with increased activity of the leukocyte-expressed NADase CD38. In this study, we tested the potential role of therapeutically targeting CD38 and NAD + in gout. Methods We studied cultured mouse wild type and CD38 knockout (KO) murine bone marrow derived macrophages (BMDMs) stimulated by monosodium urate (MSU) crystals and used the air pouch gouty inflammation model. Results MSU crystals induced CD38 in BMDMs in vitro, associated with NAD + depletion, and IL-1β and CXCL1 release, effects reversed by pharmacologic CD38 inhibitors (apigenin, 78c). Mouse air pouch inflammatory responses to MSU crystals were blunted by CD38 KO and apigenin. Pharmacologic CD38 inhibition suppressed MSU crystal-induced NLRP3 inflammasome activation and increased anti-inflammatory SIRT3–SOD2 activity in macrophages. BMDM RNA-seq analysis of differentially expressed genes (DEGs) revealed CD38 to control multiple MSU crystal-modulated inflammation pathways. Top DEGs included the circadian rhythm modulator GRP176 , and the metalloreductase STEAP4 that mediates iron homeostasis, and promotes oxidative stress and NF-κB activation when it is overexpressed. Conclusions CD38 and NAD + depletion are druggable targets controlling the MSU crystal- induced inflammation program. Targeting CD38 and NAD + are potentially novel selective molecular approaches to limit gouty arthritis.

A fly GWAS for purine metabolites identifies human FAM214 homolog medusa, which acts in a conserved manner to enhance hyperuricemia-driven pathologies by modulating purine metabolism and the inflammatory response - Tyler A. U. Hilsabeck; Ru Liu-Bryan; Tracy Guo; Kenneth A. Wilson; Neelanjan Bose; Daniel Raftery; Jennifer N. Beck; Sven Lang; Kelly Jin; Christopher S. Nelson; Tal Oron; Marshall Stoller; et al. (GeroScience, 2022)